The Effect of Passing Drill Training on Passing Accuracy Among Futsal Players at Vamos Academy Padang: PENGARUH LATIHAN PASSING DRILL TERHADAP KETEPATAN PASSING PADA PEMAIN FUTSAL VAMOS ACADEMY PADANG - Rafqi Putra, Muhammad; Umar; Irawan, Roma; Sujadesman, Bram (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of passing drill training on the passing accuracy of futsal players at Vamos Academy Padang. The research employed an experimental method using a one-group pretest–posttest design. The sample consisted of 20 futsal players from Vamos Academy Padang, selected using a total sampling technique. All participants completed a pre-test, followed by a passing drill training program conducted over 16 sessions, and then a post-test. The research instrument was a futsal passing accuracy test. Data were analyzed using descriptive statistics and a paired-samples t-test after satisfying the normality assumption. The results indicated that passing drill training had a significant effect on improving the passing accuracy of the futsal players, as evidenced by a significance value of 0.000 (p< 0.05). It can therefore be concluded that passing drill training is effective in enhancing the passing accuracy of players at Vamos Academy Padang.